2013
DOI: 10.1016/s1872-2067(12)60604-4
|View full text |Cite
|
Sign up to set email alerts
|

An atomistic thermodynamics study of the structural evolution of the Pt3Ni(111) surface in an oxygen environment

Abstract: The structural evolution of the Pt3Ni(111) surface under oxidizing conditions was studied by ab initio atomistic thermodynamics. The thermodynamic phase diagram from Ni-rich to Pt-rich conditions with oxygen coverages up to one monolayer was constructed from their 560 possible surface structures. With an increase in the oxygen chemical potential, there were only two types of thermodynamically stable structures, which were a clean Pt-skin surface and a Ni-skin surface with chemisorbed oxygen, regardless of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…DFT calculation results have demonstrated that the oxidizing atmosphere (such as O 2 or NO) could promote Ni segregating onto the surface of Pt–Ni NPs. Nevertheless, due to the weak bonding with H and C, Ni surface segregation is not remarkable in a reducing atmosphere (such as H 2 or CO) . This was also confirmed by experiments .…”
Section: Inducing Surface Segregationsupporting
confidence: 59%
“…DFT calculation results have demonstrated that the oxidizing atmosphere (such as O 2 or NO) could promote Ni segregating onto the surface of Pt–Ni NPs. Nevertheless, due to the weak bonding with H and C, Ni surface segregation is not remarkable in a reducing atmosphere (such as H 2 or CO) . This was also confirmed by experiments .…”
Section: Inducing Surface Segregationsupporting
confidence: 59%
“…[34] The lattice constant for the NiPt bulk alloy in a ratio A phase diagram was generated using atomistic thermodynamics, as described in detail in previous work. [35,36] Briefly, the most stable surface structure at a given set of chemical potentials is the one that minimizes the surface energy:…”
Section: Density Functional Theory Calculationsmentioning
confidence: 99%
“…As well known, the stability in electrochemistry is one of the critical factors to consider for its successful application to fuel cell. Consequently, the issues of surface segregation of TM in Pt 3 TM system and its loss of reactivity have become the most important problems to resolve [7,8]. Previously, the stability of Pt-3d TM system was investigated with DFT calculation, showing the structural evolution under various reaction conditions [7].…”
mentioning
confidence: 99%
“…ultrahigh vacuum condition (UHV) and CO conditions, while 3d TM-skin surface become more stable under oxidizing condition. Furthermore, the group looked into the case of oxygen induced segregation of Pt 3 Ni(1 1 1) system and calculated the corresponding phase diagram [8]. According to their calculation, under UHV condition, the Pt-skin surface is energetically more stable.…”
mentioning
confidence: 99%